Cooking with chillies : hot and spicy dishes from around the world : 150 delicious recipes shown in 250 sizzling photographs - Young, Elizabeth (Lorenz Books, 2010)
Containing a chapter on the symbolism and history of the Japanese Garden, this title examines the ancient influences that have brought Japanese gardening into the 21st century, and focuses on the essential elements of the garden, both natural and man-made. It also includes chapters on topiary, decorative artefacts and tsubukai